Biodiversity of sorghum - N. A. Kovtunova; V. V. Kovtunov (Зерновое хозяйство России, 2018)
On the basis of economic use there are three main types of sorghum: grain sorghum (Sorghum bicolor (L.) Moench), sweet sorghum (Sorghum sahharatum (L.) Pers.) and grass (Sudan) sorghum (Sorghum sudanense (Piper.) Stapf). There are various directions in the breeding work with grain, sweet and grass sorghum. However, the main breeding task of any grain crop is to create highly productive varieties and hybrids with high quality of products. This implies the involvement of new initial material with the necessary qualities in the breeding process. To solve this problem, a rich genetic material is of great need, which will be used in hybridization. The purpose of the work is to identify the main directions and results of sorghum breeding, to study biological diversity within the varieties according to individual indicators and to identify the sources of valuable traits. A large number of the identified sources of economically valuable traits, which are annually involved in hybridization with productive varieties gives evidence of the biological diversity and rich genetic material. The fulfilled work resulted in a number of developed varieties that meet the requirements of agricultural production.